We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-4
65
3
avatar+402 

Find the zeros algebraically:

 

1.) p(x) = 6x^3 + 31x^2 + 4x - 5, p(-5) = 0

 

Answer: https://web2.0calc.com/questions/find-the-zeros-algebraically-last-one

Credit to: Rom

 Feb 19, 2019
edited by GAMEMASTERX40  Feb 19, 2019
edited by GAMEMASTERX40  Feb 19, 2019
edited by GAMEMASTERX40  Feb 19, 2019

Best Answer 

 #3
avatar+5038 
+2

\(p(x) = 6x^3 + 31x^2 + 4x-5\\ p(-5)=0 \Rightarrow (x+5) \text{ is a factor}\)

 

\(\dfrac{p(x)}{x+5} = 6 x^2+x-1\\ \text{we can factor this by eye}\\ 6 x^2+x-1 = (3x-1 )(2x +1)\\ p(x) = (3x-1)(2x+1)(x+5)\\ \text{with zeros at }x = \dfrac 1 3,~-\dfrac 1 2,~-5\)

.
 Feb 19, 2019
 #1
avatar+5038 
+2

that's the problem I answered for you over in the thread you changed.

 Feb 19, 2019
 #2
avatar+402 
-3

Yeah, its that I felt bad for changing the problem after all the work you did so I posted again so it will be different. Thanks by the way!

 

-- 7H3_5H4D0W

GAMEMASTERX40  Feb 19, 2019
edited by GAMEMASTERX40  Feb 19, 2019
 #3
avatar+5038 
+2
Best Answer

\(p(x) = 6x^3 + 31x^2 + 4x-5\\ p(-5)=0 \Rightarrow (x+5) \text{ is a factor}\)

 

\(\dfrac{p(x)}{x+5} = 6 x^2+x-1\\ \text{we can factor this by eye}\\ 6 x^2+x-1 = (3x-1 )(2x +1)\\ p(x) = (3x-1)(2x+1)(x+5)\\ \text{with zeros at }x = \dfrac 1 3,~-\dfrac 1 2,~-5\)

Rom Feb 19, 2019

19 Online Users

avatar
avatar
avatar
avatar